Problematika Astronomical Twilight dalam Penentuan Awal Waktu Subuh di Indonesia - Magevira Magevira (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
Fajar Sadik plays a crucial role in determining the time for time-bound Islamic worship, specifically the Subuh (dawn) prayer and fasting. It is closely linked with the beginning of Subuh time. However, determining the exact start of Subuh remains controversial among scholars and experts, particularly regarding the Sun's angle below the horizon used as a reference point. The Indonesian Ministry of Religious Affairs has set this angle at -20°, but some studies suggest that Fajar Sadik may not appear at this angle, prompting ongoing debate and alternative proposals. This study aims to contribute to the academic discourse on determining Subuh time and seeks to bridge differences in existing criteria across Indonesia. Using an interpretive qualitative approach, the research falls under library research, relying on both printed and digital sources, as well as interviews with relevant scholars and practitioners. The findings indicate that the core issue lies in the lack of standardized methods and benchmarks for observing dawn (Astronomical Twilight). There are multiple reasons for the variation in Subuh time criteria in Indonesia. These include differing interpretations of the dawn’s color, varying geographical locations used for observation, and inconsistent usage and orientation of observational instruments. These three factors significantly influence the results of dawn observations and thus must be harmonized to minimize discrepancies. Establishing uniform standards for dawn detection is essential to achieving consensus and ensuring accurate worship timing across the country. This study underscores the importance of collaborative efforts in setting precise and agreed-upon criteria for Subuh.